THE PRODUCTION OF THE RADIOISOTOPES ¹⁶⁵ Dy, ¹⁶⁶ Ho, ¹⁷¹ Er, ¹²⁴ Sb FOR BRACHYTHERAPY USE - STAN, Oana Florina; DARABAN, L.; COSAR, C.; BARNA, B. (Studia Universitatis Babeș-Bolyai Physica, 2016)
The thermal neutron cross-sections (σ) of the reactions 164Dy(n,γ) 165Dy, 165Ho(n,γ)166Ho, 170Er(n, γ)171Er, 123Sb(n, γ)124Sb were measured by the activation method. The powder samples were irradiated in an isotropic neutron field obtained from the 241Am-Be and 239Pu-Be neutron sources, moderated with paraffin wax. The γ-ray spectra from the irradiated samples were measured by high resolution γ-ray spectrometry with a calibrated n-type Ge detector. The thermal neutron cross-sections for the reactions studied has been determined to be: for 164Dy(n,γ) 165Dy reaction 2400±200 barns, for 165Ho(n,γ)166Ho reaction 55.3±12 barns, for 170Er(n, γ)171Er reaction 1.3±2 barns and for 123Sb(n, γ)124Sb reaction 3.5±0.5 barns. The thermal neutron cross sections for the reactions 164Dy(n,γ) 165Dy, 165Ho(n,γ)166Ho and 123Sb(n, γ)124Sb are in good agreement, within limits of uncertainty, with most of the values in the literature. The thermal neutron cross section for the reaction 170Er(n, γ)171Er was not in good agreement with the values in the literature, but it is a measurement that has been made, and it can be evaluated again in the future.